PENGARUH EDUKASI PERTOLONGAN PERTAMA TEKNIK BALUT BIDAI TERHADAP PENGETAHUAN IBU PKK DI DESA PUTON KECAMATAN DIWEK KABUPATEN JOMBANG - Nur Khoiri, ahmad; Candra Permana, Arief; Paramitha Bherty, Chanda (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: First aid is a crucial initial step to prevent emergency situations from worsening before further medical treatment is provided. Injuries such as broken bones, sprains, open wounds, and strains are quite common in the community, especially at home.Methods: This quantitative study employed a pre-experimental method. The planning used was a one-group pre-test and post-test design with a cross-sectional time approach. The sample consisted of 35 women from the Family Welfare Movement (PKK) in Ngudirejo Village, Diwek District, Jombang Regency, using an incidental sampling technique.Results: The results showed a α of 0.000, which can be interpreted as a 2-tailed sig. <0.05. From these results, it can be concluded that there is an influence of First Aid Education on the Splint Bandage Technique on the knowledge of PKK mothers in Ngudirejo Village, Diwek District, Jombang Regency.Conclusion: There is an influence of First Aid Education on the Splint Bandage Technique on the knowledge of PKK mothers in Ngudirejo Village, Diwek District, Jombang Regency.